The Impact of Gender Development and Empowerment on The Economy in Sulawesi Island - Alamsyah Agit; Suhartono Suhartono; Mughni Latifah; A. Athifah Amalia Achruh P; Susilawati Muharram (Jurnal Masyarakat Maritim, 2026)
Gender development and gender empowerment are central to inclusive regional development because they shape women’s access to education, health, income, employment, political representation, and public decision-making. This study examines the effects of gender development and gender empowerment on economic growth across the provinces of Sulawesi Island. A quantitative associative design was employed using secondary data covering 2010–2024. The variables consisted of the Gender Development Index, Gender Empowerment Index, and provincial economic growth rates. Multiple linear regression was applied to assess the partial and simultaneous relationships among the variables, supported by classical assumption testing. The findings show that gender development positively and significantly affects economic growth, with a regression coefficient of 0.193 and a significance value of 0.025. Gender empowerment also has a positive and significant effect, with a coefficient of 0.175 and a significance value of 0.042. Simultaneously, both variables significantly influence economic growth, with a significance value of 0.001 and an explanatory power of 47.3 percent. These results indicate that broader and more equal access for women to human-capital development, productive employment, economic resources, leadership, and public institutions strengthens regional productivity and growth. The study concludes that gender development and empowerment should be integrated into Sulawesi’s economic policy as strategic instruments for inclusive, equitable, and sustainable development, while future research should examine institutional quality, labor-force participation, poverty, financial inclusion, and interprovincial variation across diverse provincial and sectoral economic contexts.